The Effect of Intensity News in Handling Covid-19 on Community Perception to The Government of Sukabumi City - Muhammad Tanzil Suherman; Aris Juliansyah (Institute of Computer Science (IOCS), 2021)
This study entitled The Effect of Covid-19 Handling Covid-19 Coverage Intensity on Public Perceptions of the City Government of Sukabumi. This study uses quantitative methods with path analysis. The purpose of this study was to determine the magnitude of the influence of the intensity factor on the handling of Covid-19 on public perceptions of the Sukabumi City Government. The results of this study indicate that the intensity variable has a significant effect on the perception variable. The conclusion in this study shows that the news intensity factor variable has a significant effect on the Y variable, namely perception. That by providing stimulus and information continuously, the intensity of the news will affect the perception of the audience who reads or watches the program. With good news and in accordance with the facts, the information will be easily accepted.